Log Taras Walls Construction in the Russian State in the Late 16th –Early 18th Century - Sergey Gorokhov (Нижневолжский археологический вестник)
This article reconstructs the design of crowned taras walls built in the late 16th – early 18th century in the Russian state. Based on an analysis of published written sources, archaeological and pictorial materials, the author establishes the main metric characteristics of these walls, their structural variability, and design features. The paper demonstrates that the widespread notion of taras as two parallel crowned walls with interlocks does not correspond to historical reality. The study identifies three main types of crowned taras walls: with a single wall, with double closing external walls, and with infilling of the space between double walls with soil (earth, stone, or “hryashch”, which is a type of coarse sand). The article also reconstructs the design of taras walls in Olonets based on descriptions dating back to 1649 and 1670, revealing differences in taras log cabins’ construction and the parameters. The description of the Sumskoy Ostrog (prison) of 1740 is considered an example of a wall with triangular taras log walls. The author concludes that the design of crowned taras walls is associated with the features of the defensive architecture of that period. During the Livonian War, garrisons of Russian fortresses faced the problem of wooden walls being set on fire by red-hot cannonballs. In response, a solution was found: the construction of double-row walls with the space between them filled with soil, which allowed them to successfully withstand artillery fire and prevent fires. The article presents schematic diagrams of taras wall design, as well as illustrations demonstrating their construction. This research contributes to the study of Russian fortification history and can be used for further research, as well as for the reconstruction of historical fortifications.